Effect of controlling maximum-SNR-based relay selection strategy in cooperative wireless communication systems - Essam Saleh Altubaishi (Institute of Advanced Engineering and Science, 2021)
Relay selection strategy under maximum-signal-to-noise ratio (MAX-SNR) criterion was proven to maximize performance but at the expense of losing fairness among the cooperative relays. In this work, the effect of controlling the MAX-SNR criterion on the spectral efficiency of cooperative wireless communication system with adaptive modulation is investigated. Specifically, the probability density function (PDF) of the end-to-end SNR for the considered system is derived when the controlled selection criterion is considered. Base on that PDF, the average spectral efficiency is then derived and investigated. The results show how the spectral efficiency of the system deteriorates as controlling the selection of a relay. Furthermore, the results of Monte Carlo simulation validate the derived expression.